5G standalone network's reliability, one-way latency and packet loss rate analysis for URLLC implementation - Ritola, Ville (My University, 2022)
5G is the fifth generation technology standard for cellular networks. It has three main application demands, which are Enhanced Mobile Broadband (EMBB), Massive Machine-Type Communications (MMTC) and Ultra-Reliable Low-Latency Communications (URLLC). URLLC is a very challenging demand to implement, with strict reliability and latency requirements. It has been highly specified by 2022 and 5G vendors are starting to implement basic URLLC features in the near future. The motivation for this thesis is to find ways to make measurements on how a 5G standalone (SA) network performs on key URLLC performance indicators, analyse and visualize these measurements, find reasons for certain network behavior and make estimates on what kind of impact different URLLC features will have when implemented. Furthermore, another motivation is to find a way to detect packet loss and reasons behind it, because packet loss impairs reliability significantly and should be minimized before deploying URLLC features. To measure 5G SA network's performance, four different kind of test cases were identified, in which URLLC type of network traffic is generated. There are static tests done in good coverage and bad coverage from the 5G cell, and mobility tests done by moving from good coverage to bad coverage while attached to the same 5G cell, and a handover test in which the 5G cell is changed. All tests are done in a 5G field verification environment, for both downlink and uplink. For downlink, coverage and mobility inside a cell did not have a meaningful impact to one-way latency. This was mainly because there was no need for packet retransmissions, which would have increased latency. This is promising especially for mobility URLLC use cases such as Vehicle-To-Everything communications (V2X). Uplink performed much weaker, mainly because of uplink resource scheduling and packet retransmissions. Handover was problematic for both downlink and uplink, because of the brief but massive increase in latency caused by the cell change. All packet loss in the measurements happened in uplink transmission, and this thesis includes a case study where different potential factors causing packet loss were consistently eliminated. In the end, the cause for packet loss indicates towards the 5G chipset used for the tests.
Keywords: 5G, New Radio, URLLC, reliability, latency, packet loss